2019
DOI: 10.1177/0333102419854052
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine levels and their role in the etiopathogenesis of Burning Mouth Syndrome: A systematic review

Abstract: Introduction Burning Mouth Syndrome is characterized by variable symptoms that include pain, burning and paraguesia in an otherwise healthy-appearing oral mucosa. Although the etiopathogenesis of Burning Mouth Syndrome is unknown, some studies provide evidence of subclinical inflammation leading to disrupted cytokine levels. Aim To investigate the expression of cytokines and role in the etiopathogenesis of Burning Mouth Syndrome. Methods Online databases (MEDLINE and EMBASE) were searched from November 1986 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…Our results indicated no differences in IL‐1β, IL‐2, IL‐4, IL‐6, IL‐8, IL‐10 and TNF‐α levels between BMS and controls, in adherence with previous systematic reviews 20,50 . A previous systematic review with specific focus on IL‐6 reported a majority of studies in which patients did not present increased levels of IL‐6 50 .…”
Section: Discussionsupporting
confidence: 89%
“…Our results indicated no differences in IL‐1β, IL‐2, IL‐4, IL‐6, IL‐8, IL‐10 and TNF‐α levels between BMS and controls, in adherence with previous systematic reviews 20,50 . A previous systematic review with specific focus on IL‐6 reported a majority of studies in which patients did not present increased levels of IL‐6 50 .…”
Section: Discussionsupporting
confidence: 89%
“…Although salivary proteins and hormones such as alpha-amylase, cortisol, chromogranin A, and immunoglobulin A have been shown as stress biomarkers [ 4 , 5 ], their role in the etiology of stress-related oral diseases remains unclear. The expression levels of inflammatory cytokines, including interleukins, tumor necrotic factor- α, and interferon- γ, in the saliva of patients with stress-related oral diseases have been reported previously; however, the levels have been found to vary among studies [ 6 8 ]. This might be attributed to the multiple local and systemic factors in the oral cavity that vary among individuals.…”
Section: Introductionmentioning
confidence: 91%
“…Controversial results were obtained for cytokine levels, such as in the evaluation of IL-6, where the levels were sometimes higher [86,88], sometimes comparable [83], and sometimes lower [85] for BMS patients than the controls. It remains debatable whether increased or decreased cytokine levels contribute to the etiopathogenesis of BMS [27].…”
Section: Arguments For Neuropathic Pathogenesismentioning
confidence: 99%
“…Most of them evaluated the efficacy of pharmacological and/or nonpharmacological treatments [15][16][17][18][19][20][21][22]. A few others were interested in psychological factors [23], psychophysical characterization [24][25][26], or more specifically, cytokine levels and their role in the etiopathogenesis of BMS [27]. However, no systematic review has made an inventory of all available data on primary BMS to highlight the elements leaning more towards the neuropathic or psychogenic components or hypotheses.…”
Section: Introductionmentioning
confidence: 99%